2022
DOI: 10.1037/fam0000910
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and predictors of parenting self-efficacy in new fathers.

Abstract: Parenting self-efficacy is a critical determinant of high-quality parenting behavior, but this aspect of parenting cognitions has been understudied for fathers. Longitudinal data from a sample of 182 fathers of firstborn infants in dual-earner families were used to assess how expectant fathers' rearing history, personality and personal characteristics, and family relationships were associated with their initial levels of parenting self-efficacy in the early postpartum period. Expectant fathers completed survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“… 47 Active father involvement in early parenting may yield additional benefits. 48 A better relationship between children and their fathers and a democratic paternal parenting style appeared to be associated with lower levels of emotional and behavioral problems in firstborn children. Some studies have shown that the quality of a father’s companionship has a greater coefficient of correlation with psychological and behavioral adaptation in children.…”
Section: Discussionmentioning
confidence: 98%
“… 47 Active father involvement in early parenting may yield additional benefits. 48 A better relationship between children and their fathers and a democratic paternal parenting style appeared to be associated with lower levels of emotional and behavioral problems in firstborn children. Some studies have shown that the quality of a father’s companionship has a greater coefficient of correlation with psychological and behavioral adaptation in children.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly and in sharp contrast, there exists extensive and compelling evidence for an association between parents’ self-reported attachment styles and many aspects of parenting (for a review, see Jones et al, 2015). A substantial body of research has demonstrated that an adult’s self-reports of attachment style dimensions are associated with his/her overall perceptions or expectations of current or future parenthood, perceptions of current or future parenting stress, pleasure and rewards that parents would derive from child-rearing, and/or perceptions of him/herself as a current or future parent, including parenting self-efficacy (e.g., Berant et al, 2001; Burkhart et al, 2017; Caldwell et al, 2011; Calvo & Bianco, 2015; Donithen & Schoppe-Sullivan, 2021; Howard, 2010; Kerr et al, 2019; Kohlhoff & Barnett, 2013; Moreira & Canavarro, 2016; Nathanson & Manohar, 2012; Rholes et al, 1995, 1997, 2006; Scharf & Mayseless, 2011; Spielman & Taubman-Ben-Ari, 2009; Trillingsgaard et al, 2011). Specifically, as compared to their self-reported insecure counterparts, self-reported secure parents tend to perceive parenthood as less threatening and concerning and consider parenthood as more rewarding.…”
Section: Review Of Existing Empirical Research That Is Relevant To Th...mentioning
confidence: 99%
“…To date, the identified predictors of paternal self-efficacy include fathers’ attachment style (e.g., attachment anxiety), personality traits (e.g., neuroticism), parenting role beliefs (e.g., viewing mothers as inherently better caretakers), perinatal mental health issues (e.g., affective symptoms), parenting stress, coparenting relationships, perceived social support, and family socioeconomic status (De Montigny et al, 2012; Donithen & Schoppe-Sullivan, 2021; Pinheiro, 2014; Pinto et al, 2016). Moreover, there also exists a slim body of research surveying both mothers and fathers (Biehle & Mickelson, 2011a, 2011b; Fang et al, 2022; Giallo, Treyvard, et al, 2013; Knauth, 2000; Leerkes & Burney, 2007; Murdock, 2013; Riina & Feinberg, 2012; Sevigny & Loutzenhiser, 2010).…”
Section: Evaluation Of the Potential Utility Of Our Proposed Model Fo...mentioning
confidence: 99%
See 1 more Smart Citation
“…in the lives of children, it is also true that they often perceive their role as being mediated by mothers [104,105], thus still perceiving the ability to successfully perform the parenting role as more maternal than paternal. Also, especially in the Italian context, mothers usually spend more time with their children than fathers, which may render child characteristics, especially behavioral problems, more of a challenge for mothers than fathers.…”
Section: Plos Onementioning
confidence: 99%